Islamic Republic of Mauritania : Turning Challenges into Opportunities for Ending Poverty and Promoting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2017)
The systematic country diagnostic (SCD) of Mauritania seeks to identify key constraints and priority interventions needed for the country to achieve the twin goals of the World Bank Group: (i) ending extreme poverty; and (ii) improving shared prosperity among the poorest forty percent of the population (the bottom 40). The analysis steps back from the World Bank Group’s existing portfolio to conduct a broad overview of the country’s socioeconomic development. The SCD is designed as an analytical input for stakeholders to debate development priorities. It was undertaken during the period in which the government was developing a new accelerated growth and shared prosperity strategy (strategie de croissance acceleree et prosperite partage, SCAPP). The diagnostic draws on an extensive knowledge base and presents findings and conclusions in an accessible format geared towards stimulating dialogue with the authorities and relevant stakeholders. The SCD is derived principally from the wealth of recent analysis by the World Bank Group and other sources. While studies were undertaken during the course of the SCD preparation to complement the existing analytical knowledge base, important knowledge gaps remain. The SCD identifies these gaps and presents a range of issues for further analysis.